Oral History Interview with Kaying Xiong by Emily Wievel - Wievel, Emily; Xiong, Kaying (My University, 2009)
This interview is part of an oral history project conducted in honor of 25th anniversary of the Women's Studies Program at the University of Wisconsin - Eau Claire. Dr. Katherine A. Rhoades, Dean and Professor Emerita and Interim Women's Studies Program Coordinator, developed the question protocol. Students in her WMNS 490: Feminist Analysis and Practices conducted interviews with eight feminists in and around Eau Claire, Wisconsin. Students also created "digital stories," or short documentaries, using interview excerpts and photographs.